(untitled) (Kerala Journal of Psychiatry, 2018)
Nonverbal communication refers to how people communicate, intentionally or unintentionally, without words. A study was conducted in general and taluk hospitals of Kottayam to develop a scale to measure pain behaviour: Scale of Pain Expression Behaviours (SOPEB). Consecutive patients brought to the hospitals with diabetic foot ulcer (n=350) were given SOPEB. They were also given Adult Nonverbal Pain Scale. We determined content validity index. Construct validity for SOPEB was computed through exploratory factor analysis. These factors concentrate and index the dispersed information in the original data and replace 105 characteristics to 25 characteristics in each domain. Kaiser-Meyer-Olkin Test values was 0.602, and it determines suitability of data for factor analysis. After rotation, it identified five linear components which gave eigenvalue of more than 1. A Scree Plot was used to visually assess which components or factors explain most of the variability in the data. Concurrent validity is used to correlate SOPEB scores with adult Nonverbal Pain Scale. The reliability of each item was calculated using percent agreement and the Cohen’s Kappa coefficient. Nonverbal communication has a key role in patient care. Effective communication takes into account nonverbal communication also. Usage of tools such as SOPEB helps to assess the proper quantification of pain behaviour.